PENINGKATAN MUTU PENDIDIKAN MELALUI IMPLEMENTASI MANAJEMEN PENINGKATAN MUTU BERBASIS SEKOLAH (MPMBS) PADA MTsN DI KOTA BENGKULU - Hj. Khairiah; H Syarifuddin (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2018)
The objective of this research was to describe the implementation of the school-based management quality in achieving the educational quality at the public MTs in Kota Bengkulu. The design of this research used  a descriptive one  the  data  were  collected by using  a set of instrument ; i.e. interview, observationand documentation. The results ahow  that  the otonomi, responsibility, authority, participation, transparency, accountability, equality, equity  and  sus- tainability has not yet been optimally applied. So it can be suggested if you want to improve the quality of education then implement the program MPMBS